Kanjan Serayong Traditional Death Ceremony : Shifting Values of Pesaguan Dayak People Due to Mondial Religion - Fitriana, Rossa; Putri, Nadila; Darmawan, Diaz Restu (Universitas Tanjungpura, 2024)
This study aims to describe the procession of the Kanjan Serayong ceremony and the impact of the entry of the Mondial religion, namely Catholicism. This paper has explained the consequences of the traditional beliefs and culture of the Pesagan Dayak community and described the values contained in the Kanjan Serayong ceremony. Data collection in this study used qualitative methods with an ethnographic approach in the Upper Pesaguan Dayak community located in Beringin Rayo Village, Tumbang Titi District, Ketapang Regency. Research data were collected through observation, interviews, documentation, and literature studies. This research found that in the Kanjan Serayong ceremony, there were several shifts from ceremonial processions in ancient times, such as shifts in ceremonial processions, changes in tools and materials used in ceremonies and changes in meaning and meaning. The value of public trust. The shift in the Kanjan Serayong ceremony was caused by the entry and spread of the Mondial religion in the life of the Pesaguan Dayak community in Tumbang Titi District. Then, the impact of the entry of Catholicism also changed the values and even some new values in the Kanjan Serayong ceremony. Cultural values at the traditional Kanjan Serayaong ceremony are related to social, religiosity, and entertainment values.